LIKUIDITAS DAN RISIKO SISTEMATIS TERHADAP TINGKAT PENGEMBALIAN SAHAM PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Elfiswandi, Elfiswandi (Jurnal Ekobistek, 2013)
Abstract - The objectives of this research are to analyze to what extent liquidity and systematic risk individually affect stock returns of LQ45 Companies at the Indonesia Stock Exchange, and to analyze to what extent both liquidity and systematic risk simultaneously affect stock returns in LQ45 Companies at the Indonesia Stock Exchange. Factors that affect stock returns of LQ45 companies are companies? liquidity, investment risk, inflation, market interest rate and market price fluctuations. The research method used in this paper is a descriptive study, that is done by analyzing the secondary data of LQ45 companies at the Indonesia Stock Exchange. In this study, the author used a purposive sampling technique. Data is collected by using a literature study, by visiting the Capital Market Information Center of the Indonesia Stock Exchange in Padang and by using the internet. The method of data analysis used is time series multiple regression model and the hypotheses were tested by using T-test statistics and F-test statistics at the 5% level of significance. The T-test results showed that only systematic risk has a significant effect on stock returns, whereas Liquidity has no effect on stock returns. On the contrary, F-test results found that both liquidity (Current Ratio) and systematic risk (?) simultaneously have significant effects on stock returns. Keyword: Liquidity, Systematic Risk , dan Stock Returns.